Multi-objective optimization of a hybrid biomass-based SOFC/GT/double effect absorption chiller/RO desalination system with CO2 recycle. (1st February 2019) - Behzadi, A.; Habibollahzade, A.; Zare, V.; Ashjaee, M.
Highlights: A SOFC/GT/Chiller/RO system is proposed for power/cooling/fresh water production. Proposed integrated system is compared from exergy/exergoeconomic viewpoints. The new system is optimized by multi-objective optimization method. Exergy efficiency and cost are 38.16% and 69.47 /GJ at optimum point. Abstract: In this study, a biomass-based solid oxide fuel cell integrated with a gas turbine, a reverse osmosis desalination unit, and double-effect absorption chiller is proposed for power generation, cooling and fresh water production. Accordingly, environmental contamination of the proposed system is mitigated by capturing and recycling emitted CO2 into the gasifier. Subsequently, a parametric study is performed to analyze the proposed multi-generation system from energy, exergy, exergoeconomic, and environmental impact viewpoints. In addition, considering the exergy efficiency as a performance indicant (to be maximized) and total product cost as an economic indicator (to be minimized) multi-objective optimization is implemented to ascertain the best operating conditions. The results of exergy and exergoeconomic analysis reveal that gasifier is the primary source of irreversibility with exergy destruction rate of 179.8 kW and the exergoeconomic factor of the cooling system components is lower than 20%. Multi-objective optimization results show that exergy efficiency and total product unit cost of the proposed system is 38.16% and 69.47 /GJ, respectively at the optimum operating condition. Furthermore, scatter distribution of the effective parameters demonstrates that, the stack temperature difference, gas turbine pressure ratio and CO2 recycling ratio are the most sensitive parameters, which should be kept at their lowest value.